Discovery Learning to Develop Student Reflective Thinking Ability and Self-Efficacy - Listyotami, Mega Kusuma; Noer, Sri Hastuti; Haenilah, Een Yayah (Universitas Islam Raden Intan Lampung, INDONESIA, 2018)
The research and development aims to produce a discovery learning model that is oriented towards the student ability of reflective thinking and self-efficacy. The research was conducted using the Research and Development (R and D) method. The research and development model used refers to the procedure of R and D development by Gall and Borg by Sukmadinata that is ADDIE. The steps for implementing the research and development strategy include; (1) analysis, (2) design, (3) development, (4) implementation, (5) evaluation. The Data collecting methods and instruments are used tests and non-tests. The Data collection techniques using observation, interviews, questionnaires, and tests. The Data analysis techniques used in research and development are quantitative and qualitative descriptive. The results showed that the discovery learning model that was oriented towards the student ability of reflective thinking and self-efficacy was effective to improve the student ability of reflective thinking and self-efficacy respectively by 77% and 30%.Keywords: Discovery Learning, Relative thinking, dan Self-Efficacy